2014
DOI: 10.1021/ar500097m
|View full text |Cite
|
Sign up to set email alerts
|

Efficient and Accurate Fragmentation Methods

Abstract: Three novel fragmentation methods that are available in the electronic structure program GAMESS (general atomic and molecular electronic structure system) are discussed in this Account. The fragment molecular orbital (FMO) method can be combined with any electronic structure method to perform accurate calculations on large molecular species with no reliance on capping atoms or empirical parameters. The FMO method is highly scalable and can take advantage of massively parallel computer systems. For example, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
97
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 96 publications
(101 citation statements)
references
References 56 publications
0
97
0
Order By: Relevance
“…For modeling intermolecular interactions, similar strategies based on multipolar expansion have been utilized. [39][40][41] Recently, EFP was combined with fragment molecular orbital (FMO) method 42 giving rise to the EFMO method capable of describing both molecular aggregates and large molecules 43,44 (however, EFMO method has not yet been extended to excited states). Detailed reviews of various flavors of fragment-based methods can be found in Refs.…”
mentioning
confidence: 99%
“…For modeling intermolecular interactions, similar strategies based on multipolar expansion have been utilized. [39][40][41] Recently, EFP was combined with fragment molecular orbital (FMO) method 42 giving rise to the EFMO method capable of describing both molecular aggregates and large molecules 43,44 (however, EFMO method has not yet been extended to excited states). Detailed reviews of various flavors of fragment-based methods can be found in Refs.…”
mentioning
confidence: 99%
“…The FMO method is particularly appealing in this regard since the code is highly scalable and is therefore able to make efficient use of massively parallel computer systems. 33,65,66 …”
Section: Discussionmentioning
confidence: 99%
“…Over the years, a number of fragment‐based methods have been devised to accurately compute energies of larger molecules . These methods incorporate a general approach, where the large system is described by smaller fragments that are treated at the same geometry that they have in the target molecule.…”
Section: Introductionmentioning
confidence: 99%
“…Over the years, a number of fragment-based methods have been devised to accurately compute energies of larger molecules. [24][25][26][27][28][29][30][31][32][33][34][35][36][37] These methods incorporate a general approach, where the large system is described by smaller fragments that are treated at the same geometry that they have in the target molecule. The total energy of the large system is obtained directly from the energies of smaller (typically overlapping) frag-ments that contain only their local interactions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation